2017
DOI: 10.1111/jcmm.13288
|View full text |Cite
|
Sign up to set email alerts
|

LINC01101 and LINC00277 expression levels as novel factors in HPV‐induced cervical neoplasia

Abstract: Recently long non‐coding RNAs were identified as new factors involved in gene expression regulation. To gain insight into expression pattern of these factors related to E7 HPV18 oncogene, this study uses HeLa cell culture transfected with E7‐siRNA. Gene expression profile was investigated using microarray analysis. After analysing the microarray results, we identified 15,387 RNA species differentially expressed in E7‐siRNA‐transfected cells compared with controls (fold change >2). The expression profiles of ln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…LncRNA is a class of transcript with more than 200 nucleotides in length, but do not encode proteins . Aberrant expressions of lncRNAs have been revealed in various pathological status, particular in cancers . Furthermore, lncRNAs also play important roles in various pathophysiological processes, including cancers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNA is a class of transcript with more than 200 nucleotides in length, but do not encode proteins . Aberrant expressions of lncRNAs have been revealed in various pathological status, particular in cancers . Furthermore, lncRNAs also play important roles in various pathophysiological processes, including cancers .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Aberrant expressions of lncRNAs have been revealed in various pathological status, particular in cancers. [10][11][12][13] Furthermore, lncRNAs also play important roles in various pathophysiological processes, including cancers. [14][15][16][17][18] In NSCLC, several lncRNAs are reported to participate in tumourigenesis and/or development of NSCLC.…”
mentioning
confidence: 99%
“…Increasing studies revealed that lncRNAs play an effect on several cellular functions such as cell growth, development, migration, differentiation, metabolism, and many other cell biological processes (Gao, Lv, Li, Han, & Zhang, 2017;Iancu et al, 2017;G. Wang, Pan, Zhang, Wei, & Wang, suppressor gene in several tumors (L. H. Liu, Yue, et al, 2016;Xu et al, 2018;Yang et al, 2017;C.…”
mentioning
confidence: 99%
“…Of these, the majority were noncoding RNAs (66%) followed by microRNAs (16%), antisense RNAs (10%), pseudogenes (5%), small nucleolar RNAs (3%), and small nuclear RNAs (<1%). (B) A table of selected characterized noncoding RNA genes bound by TRP47 showing that many are involved cell proliferation or apoptosis and some are also bound by another ehrlichial TRP: NR_027181.1 [ 23 ], NR_029833.1 [ 24 ], NR_029608.1 [ 25 ], NR_126415.1 [ 26 ].…”
Section: Resultsmentioning
confidence: 99%